2019
DOI: 10.1124/dmd.119.087031
|View full text |Cite
|
Sign up to set email alerts
|

Arylacetamide Deacetylase Enzyme: Presence and Interindividual Variability in Human Lungs

Abstract: Human arylacetamide deacetylase (AADAC) is a single microsomal serine esterase involved in the hydrolysis of many acetyl-containing drugs. To date, the presence and activity of the AADAC enzyme in human lungs has been scarcely examined. We investigated its gene and protein expression as well as interindividual variations in AADAC activities in a large number of human lungs (n 5 25) using phenacetin as a selective substrate. The kinetic parameters K m and V max were determined. Our findings highlighted a high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(29 reference statements)
0
3
0
Order By: Relevance
“… 41 , 44 Furthermore, Gabriele et al discovered the presence and inter-individual variation of AADAC in the human lung. 64 These findings suggest the important role of AADAC pharmacogenetics in tuberculosis drug therapy.…”
Section: Discussionmentioning
confidence: 90%
“… 41 , 44 Furthermore, Gabriele et al discovered the presence and inter-individual variation of AADAC in the human lung. 64 These findings suggest the important role of AADAC pharmacogenetics in tuberculosis drug therapy.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, Fukami et al conducted kinetic and inhibition studies in human liver microsomes and identified AADAC as the enzyme that metabolizes ketoconazole to DAK (Fukami et al, 2016). AADAC is expressed in the liver and small intestine and is also present in the lungs at a lower level (Figure 2) (Gabriele et al, 2019;Fukami et al, 2022). Overexpression of AADAC in ovarian cancer tissues has been found to promote therapeutic activity of cisplatin and imatinib against ovarian cancer cells (Wang et al, 2022).…”
Section: Arylacetamide Deacetylase (Aadac)mentioning
confidence: 99%
“…Gabriele and colleagues not only demonstrated the presence of AADAC protein in the lung through immunoblot analysis but also observed high interindividual variability in both AADAC mRNA levels and the enzymatic activity in hydrolyzing phenacetin, a known AADAC substrate (Gabriele et al, 2019). The impact of SNPs on the AADAC's activity hydrolyzing eslicarbazepine acetate was studied in small intestine and liver microsomes (Hirosawa et al, 2021), where samples with the SNPs R248S or X400Q showed lower activity than the wild type (5% or 21%, respectively), and those with V172I showed higher activity than the wild type (174%).…”
Section: Pharmacogenetics Of Aadacmentioning
confidence: 99%